Freedom of religion and religious coercion The challenge posed by the prohibition of coercion as a condition of religious freedom - Pretorius, SP (Nederduitse Gereformeerde Teologiese Tydskrif, 2013)
Religious freedom opened up a world for religious diversity. Te drafters of the right to freedom of religion were well aware of the atrocities committed in the name of religion and therefore include an important fundamental of religious freedom. Belonging to and participating in the practises of religion must be a voluntary act. Unfortunately, as a result of the susceptibility of people and the nature of religion some new religious groups feel entitled to ignore the condition believing that their belief system supersedes any earthly convention. Addressing this issue pose a challenge to governments. Restricted by the right to religious freedom no political or legal measure can be introduced to regulate or prescribe the internal functioning of religion. The solution is needed on another level. The South African charter for religious rights and freedoms not only provides an ideal platform to engage in a fruitful interaction with other religions but also to guard and assist in the adherence to the fundamentals of religious freedom.